Immunogenicity and safety of 11- and 12-valent pneumococcal non-typeable Haemophilus influenzae protein D-conjugate vaccines (11vPHiD-CV, 12vPHiD-CV) in infants: Results from a phase II, randomised, multicentre study. Issue 1 (3rd January 2019) - Carmona Martinez, Alfonso; Prymula, Roman; Miranda Valdivieso, Mariano; Otero Reigada, Maria del Carmen; Merino Arribas, Jose Manuel; Brzostek, Jerzy; Szenborn, Leszek; Ruzkova, Renata; Horn, Michael R.; Jackowska, Teresa; Centeno-Malfaz, Fernando; Traskine, Magali; et al.
Highlights: 11-/12-valent vaccines include 10 PHiD-CV conjugates + 19A(11v) + 6A(12v) CRM-conjugates. 11vPHiD-CV and 12vPHiD-CV were administered to infants according to a 3 + 1 schedule. Immunogenicity was compared to PHiD-CV (common serotypes) and PCV13 (19A and 6A). Post-dose 3 immune responses to investigational vaccines were non-inferior to comparators. Safety and reactogenicity profiles of 11v/12vPHiD-CV were comparable to that of PHiD-CV. Abstract: Background: We assessed 2 investigational 11- and 12-valent vaccines, containing capsular polysaccharides of 10 serotypes as in the pneumococcal non-typeable Haemophilus influenzae protein D-conjugate vaccine (PHiD-CV) and CRM197 -conjugated capsular polysaccharides of serotypes 19A (11-valent) or 19A and 6A (12-valent). Methods: In this phase II, partially-blind, multicentre study (NCT01204658), healthy infants were randomised (1:1:1:1) to receive 11vPHiD-CV, 12vPHiD-CV, PHiD-CV, or 13-valent CRM197 -conjugate pneumococcal vaccine (PCV13), at 2, 3, and 4 (primary series), and 12–15 months of age (booster dose), co-administered with DTPa-HBV-IPV/Hib. Confirmatory objectives assessed non-inferiority of investigational vaccines to comparators (PHiD-CV for common serotypes; PCV13 for 19A and 6A), in terms of percentage of infants with pneumococcal antibody concentrations ≥0.2 μg/mL and antibody geometric mean concentrations, post-primary vaccination. Reactogenicity and safety were assessed. Results: 951 children received ≥1 primary dose, 919 a booster dose. Pre-defined immunological non-inferiority criteria were met simultaneously for 9/11 11vPHiD-CV serotypes (all except 23F and 19A) and 10/12 12vPHiD-CV serotypes (all except 19A and 6A); thus, non-inferiority objectives were reached. For each PHiD-CV serotype, percentages of children with antibody concentrations ≥0.2 µg/mL were ≥96.7% post-primary (except 6B [≥75.2%] and 23F [≥81.1%]), and ≥98.1% post-booster vaccination. For each PHiD-CV serotype except serotype 1, ≥81.0% and ≥93.9% of children had opsonophagocytic activity titres ≥8, post-primary and booster vaccination. AEs incidence was similar across all groups. SAEs were reported for 117 children (29 in the 11vPHiD-CV group, 26 in the 12vPHiD-CV group, 38 in the PHiD-CV group and 24 in the PCV13 group); 4 SAEs were considered vaccination-related. No fatal events were recorded. Conclusion: Addition of 19A and 6A CRM197 -conjugates did not alter immunogenicity of the PHiD-CV conjugates; for both investigational vaccines post-booster immune responses to 10 common serotypes appeared similar to those elicited by PHiD-CV. Safety and reactogenicity profiles of the investigational vaccines were comparable to PHiD-CV. Clinical trial registry: NCT01204658.